Memory impairment in rats by hippocampal administration of the serine protease subtilisin - Kornisiuk, Edgar Ernesto (2011)
Since the serine protease subtilisin has been reported to generate a novel form of long-term depression (LTD) in rat hippocampal slices, the present work was designed to determine whether it has any effect on learning and memory processes. Rats were used to examine the effects of subtilisin, injected directly into the dorsal hippocampus, on task performance in a step-through inhibitory avoidance of a mild footshock. The administration of 100. ng of subtilisin into each hippocampus, immediately after training, was sufficient to induce a detectable learning deficit with a footshock stimulus of 0.5. mA. Higher doses produced dose-related impairments in memory consolidation. These effects were not the result of irreversible toxicity, since rats trained with a higher amplitude footshock (0.75. mA) were able to perform as control animals; therefore, the amnesic effect was not further evident. Furthermore, the administration of subtilisin before avoidance training did not produce any detectable effect on performance during the training or test sessions, indicating that neither acquisition nor consolidation was affected. It is concluded that the post-training administration of a serine protease inhibitor is able to produce robust deficits of memory consolidation consistent with its ability to generate LTD, raising the possibility that related molecules could play physiological or pathological roles in the modulation of learning and memory. © 2010 Elsevier B.V.